Endothelial-Myocardial Angiocrine Signaling in Heart Development - Kim, Hyeonyu; Wang, Mingqiang; Paik, David T. (Frontiers in Cell and Developmental Biology, 2021)
Vascular endothelial cells are a multifunctional cell type with organotypic specificity in their function and structure. In this review, we discuss various subpopulations of endothelial cells in the mammalian heart, which spatiotemporally regulate critical cellular and molecular processes of heart development via unique sets of angiocrine signaling pathways. In particular, elucidation of intercellular communication among the functional cell types in the developing heart has recently been accelerated by the use of single-cell sequencing. Specifically, we overview the heterogeneic nature of cardiac endothelial cells and their contribution to heart tube and chamber formation, myocardial trabeculation and compaction, and endocardial cushion and valve formation via angiocrine pathways.